2021
DOI: 10.2147/ijgm.s335817
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of the Expression of FEN1 in Primary Osteosarcoma

Abstract: The aim of this research was to investigate the clinical significance of the expression of flap structure-specific endonuclease 1 (FEN1) in primary osteosarcoma. Methods: The expression of FEN1 was detected by immunohistochemistry analysis. The association of the expression of FEN1 in osteosarcoma with clinicopathological parameters was analyzed by using χ 2 test or Fisher's exact test. Survival analyses were performed by Kaplan-Meier method and Cox proportional hazards regression model. Results: Of the 40 ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It was documented that dysregulation of expression or mutation in FEN1 in normal cells leads to provoking various diseases, such as cancers [58]. Moreover, our data were conflicting with the literature supporting its overexpression that contributes to drug resistance and it suggests targeting this gene, which has been verified as an effective strategy in mono-or combination therapy for many cancers [59]. Our information is in contradiction with previous studies considering FEN1 as a marker of multiple metastatic tumors and poor prognosis [60] and is viewed as an effective target for tumor resistance treatment [61].…”
Section: Discussioncontrasting
confidence: 72%
“…It was documented that dysregulation of expression or mutation in FEN1 in normal cells leads to provoking various diseases, such as cancers [58]. Moreover, our data were conflicting with the literature supporting its overexpression that contributes to drug resistance and it suggests targeting this gene, which has been verified as an effective strategy in mono-or combination therapy for many cancers [59]. Our information is in contradiction with previous studies considering FEN1 as a marker of multiple metastatic tumors and poor prognosis [60] and is viewed as an effective target for tumor resistance treatment [61].…”
Section: Discussioncontrasting
confidence: 72%
“…15 This proliferative activityrelated property has also been noted in cancer cells, where FEN1 overexpression has been associated with accelerated progression and shorter survival periods. [16][17][18][19] Notably, an abnormal DNA damage repair process not only induces the production of neoantigens on the cell surface, 8 but also affects PD-L1 expression through the JAK/STAT1 signaling pathway and interferon stimulator genes (ISGs), 20,21 raising the question of whether interfering with FEN1 gene expression can simultaneously affect PD-L1 and HLA/MHC levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Shang et al reported increased levels of sphingolipid and ceramides in patients with acute gout, suggesting that the onset of gout was related to the sphingolipid metabolism pathway [18]. Acute onset of gout is known to be related to gout crystals that stimulate the formation of NALP3 in ammasome by monocytes and promote the release of in ammatory factors (IL-2 and TNF-α) to act on joint synovium, which further causes in ammation expansion [19]. TNF-α is an in ammatory factor that can stimulate the production of sphingolipid by the mitochondria.…”
Section: Relationship Between Lipid Metabolism Pathway and Acute Atta...mentioning
confidence: 99%